2015
DOI: 10.1002/app.42022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose‐functionalized multiwalled carbon nanotubes on the structural, mechanical, and thermal properties of chitosan nanocomposite films

Abstract: A series of multiwalled carbon nanotubes (MWCNTs) grafted by chitosan nanocomposite (NC) films were prepared by a direct blending process and solution casting method. In this study, we modified multiwalled carbon nanotubes with glucose (MWCNT–Gl) for this purpose, and the effects of MWCNT–Gl on the structural, mechanical, and thermal properties of chitosan films with different contents of MWCNT–Gl were investigated. The structure, thermal stability, and mechanical properties of the composite were examined by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As it was shown in the Table , the elongation of NCs was increased than the pure PVA. It is because of decreasing of the hydrogen bonding interactions and increasing of the free volume between polymer chains after incorporation of NPs into the polymer matrix …”
Section: Characterization Methodsmentioning
confidence: 99%
“…As it was shown in the Table , the elongation of NCs was increased than the pure PVA. It is because of decreasing of the hydrogen bonding interactions and increasing of the free volume between polymer chains after incorporation of NPs into the polymer matrix …”
Section: Characterization Methodsmentioning
confidence: 99%
“…The main reason for this observation maybe due to decreasing the intermolecular interactions density in the polymer chains and increasing the free volume between the polymer chains after incorporation with NPs. It indicate that the NC films were more flexible than the neat polymer .…”
Section: Resultsmentioning
confidence: 89%
“…Hence, the increase in tensile strength and modulus may be attributed to the reinforcing effect of MWCNTs on the matrix, due to the interfacial adhesion between polymer matrix and nanofillers. Various researchers reported on the mechanical properties of polymer nanocomposites reinforced with CNTs and have shown that CNTs are excellent reinforcing agents for polymer matrices . Spitalsky et al .…”
Section: Resultsmentioning
confidence: 99%